Changes in optical properties, structure and chemical composition of thin-film Ag-Pbl₂ systems at intercalation of ammonia - Mussil, V.V.; Lemeshevskaya, Ye.T.; Pilipenko, V.V.; Gurina, G.I. (Functional Materials, 2008)
The results of optical, electron microscopic and electron diffraction studies of film Pbl₂ and two-layer photosensitive Ag-Pbl₂ systems and changes thereof under ammonia intercalation are reported. The effect of intercalation on the photographic characteristics of the samples (photosensibility and contrast) has been established. The reversible changes in diffraction efficiency of photoinduced periodic structures have been revealed. The observed phenomena are discussed taking into account the concepts of the granular film optics and waveguide coatings, as well as of the chemical reaction kinetics. Представлено результати оптичних, електронно-мікроскопічних і електронографічних досліджень плівок Pbl₂ та двошарових світлочутливих систем Ag-Pbl₂ і їх змін за умови інтеркаляції аміаку. Встановлено вплив інтеркаляції на фотографічні характеристики зразків: світлочутливість і контрастність. Виявлено оборотні зміни дифракційної ефективності фотоіндукованих періодичних структур. Явища, які спостерігаються, обговорено з урахуванням концепцій оптики гранулярних плівок і хвилеводних покриттів, а також закономірностей кінетики хімічних реакцій. Представлены результаты оптических, электронно-микроскопических и электронографических исследований пленок Pbl₂ и двухслойных светочувствительных систем Аg-Pbl₂ и их изменений при интеркаляции аммиака. 'Установлено влияние интеркаляции на фотографические характеристики образцов: светочувствительность и контрастность. Обнаружены обратимые изменения дифракционной эффективности фотоиндуцированных периодических структур. Наблюдаемые явления обсуждены с учетом представлений оптики гранулярных пленок и волноводных покрытий, закономерностей кинетики химических реакций.